Degree Centrality of a Brain Network Is Altered by Stereotype Threat: Evidences From a Resting-State Functional Magnetic Resonance Imaging Study - Wu, Xin; Zhao, Yufang (Frontiers in Psychology, 2021)
Previous studies have found effects of stereotype threat (ST) on cognitive processes, emotions and motivations which could account for the underperformance in domain tasks. Efficient brain function does not require the functions of different brain regions during specific tasks, but it requires the brain networks on which information be transported. Based on this, ST’s effects on degree centrality of rest-stating state (RSDC) was investigated under math ST. The results showed that RSDC was decreased in right anterior temporal lobe (ATL) and left hippocampus, while the RSDC was increased in left precuneus, left angular gyrus (AG) and middle frontal gyrus (MFG) under ST. The functional analysis of these regions in Neurosynth showed that left hippocampus was related to the negative emotions, the left AG and left MFG were related to memory retrieval and left precuneus was related to autobiographical memory or episodic memory. These results might reflect that individuals might be attempting to inhibite the negative emotions induced by ST, at the some time increasing the self-concerning by retrieving episodic memory or autobiographical memory.